Master Plan of local E-government for Village Office Information System Refer to Ministerial Regulations on Work Procedures - Meme Susilowati; Yudhi Kurniawan; C Lenny; Wedha Adistianaya Dewa; Moh Ahsan (Universitas PGRI Kanjuruhan Malang, 2021)
This article contains a local e-government master plan with a case study in a village in Malang district. The master plan referred to the Ministerial regulation regarding the Organizational Structure and Work Procedure of Village Administration. This research method will begin with data gathering (literature study, observation, interview), analysis of SRS (Software Requirement and Specification) documents for synchronization with division of work tasks, creating focus groups, making Master Plan. This article also will present a focus group diagram on the division of labour results based on the 2015 ministerial regulation. Then proceed with a master plan diagram based on the requirement of the actor system in the village office. Namely the village head, village secretary, 3 heads of affairs (administration, finance, planning) and a section head. This article will present 13 names and descriptions of applications needed to support the administrative system at the village office. This article also provides 58 tables needed for a Master Plan of Local E-government for village office information system refer to ministerial regulations on work procedures